Some cases of student misbehavior in the Mountain Provincial High School, Bontoc, Mountain Province, and their relationship with certain cultural practices - Sumedca, Alexander ([Quezon City s.n.], 1964)
This study inquired on the relationships between old cultural practices and new social changes which can explain delinquent behavior by examining eight cases of delinquent behavior in the Mountain Provincial High School which are typically recurrent. In order to provide the proper perspective for the description and analysis of these cases, the writer gives a brief account of the socio-cultural background of the locality-- outstanding traits, complexes, and institutions of the culture, like the OLOG and the ATO.
Thesis (M.Ed.)--University of the Philippines
Keywords: Juvenile delinquency -- Case studies; Bontoc, Mountain Province